PLAST Classification of Mandibular Duplication and Associated Anomalies. Issue 2 (June 2023) - Leberfinger, Ashley N.; Murthy, Ananth S.
Mandibular duplication is a rare subtype of craniofacial duplication. It is often associated with other anomalies including cleft palate, lingual duplication, and macrostomia. We present an 8-year-old female who had mandibular duplication presenting soon after birth with tongue-based airway obstruction. She was found to have cardiac abnormalities, split sternum, accessory tongue, cleft palate, and accessory submandibular gland. She underwent surgical correction including resection of the duplicated mandible, tongue, and submandibular gland as well as tongue lip adhesion at 12 days old. Post operatively, we were able to avoid tracheostomy and she was able to undergo successful correction of her cardiac anomaly. Literature review found 29 patients with mandibular duplication. Patients with w-shaped (type I) mandibular duplication are more likely to have airway compromise requiring intervention. Several associated anomalies were seen in patients with mandibular duplication. After analysis, we propose the PLAST classification to describe common findings: cleft Palate, Lip duplication, Airway obstruction, Salivary gland abnormalities, and Tongue duplication. Extra craniofacial anomalies such as cardiac and spinal anomalies were also noted in several patients.